Octreotate avid intrapancreatic lesions-intrapancreatic splenunculi masquerading as pancreatic neuroendocrine tumours - Addis, Bridget T.; Chai, Debbi; Navadgi, Suresh (International Surgery Journal, 2026)
Splenunculi (heterotopic spleens or accessory splenic tissue), are relatively common (occurring in 10-30% of the population) and can occur in a variety of locations, including within solid organs such as the pancreas, kidney and the liver. The majority of intrapancreatic splenunculi (IPS) are located within or adjacent to the tail of the pancreas. Differentiating IPS from other pancreatic lesions, specifically those with malignant potential such as pancreatic neuroendocrine tumours (pNETs) can be challenging based solely on radiological appearance. Both IPS and pNETs have similar characteristics on contrast enhanced CT and octreotate-PET imaging. IPS are benign and largely asymptomatic. They require no surgical intervention or follow-up. pNET’s are relatively rare neoplasms which require active surveillance or surgical resection depending on their size and other patient factors. Current international guidelines do not routinely recommend definitive tissue diagnosis prior to proceeding with surgical resection of presumed pNET lesions. Here, we present a case series of four patients with tail of pancreas (ToP) lesions, initially suspected to be pNETs based on CT and octreotate PET imaging, who subsequently underwent further, more sensitive investigations (denatured red cell scan or endoscopic ultrasound (EUS) guided fine needle aspirate (FNA) and were confirmed to have IPS. Accurate diagnosis with further investigations such as EUS guided biopsy, is valuable in guiding surgical management of octreotate avid ToP lesions and avoiding potentially harmful and unnecessary surgical intervention.